Thermal Analysis Of Solid Waste Gasifier-combustor. - Idroas, M.Y.; Miskam, M.A.; Zainal, Z. A.; Mustafa, K.F. (2004)
The increase of municipal solid waste generated in Malaysia has become a critical issue. In year 200 I, the amount of solid waste produced in Malaysia is 16,247 tons per day and the rate is continue increasing until today. Besides, landfills are slowly being used up and land for landfill will be scrace mainly due to the increase of population and rapid development of the country.